The application of human resources information systems for enhancing output in agricultural companies - Prasad, KDV; Nag, Debanjan; Kalavakolanu, Sripathi; Vaidya, Rajesh (Journal of Social Economics Research, 2023)
To examine whether the application of integrated human resource information systems can enhance output, increase productivity, and reduce operating costs in agricultural companies. Survey method is used in this study. One hundred and forty-five supply chain employees from the agricultural industry were surveyed through a structured questionnaire to find the influence of HRIS in the recruitment process, performance appraisal, training needs, and management support to enhance output. The data were analyzed using statistical methods like correlation analysis, Chi-square analysis, and factor analysis. The results reveal that four factors-recruitment process, performance appraisal, training needs, and management support are statistically significant and influence the outcome variable enhancing output. The automated HRIS system can be helpful in managing the recruitment process, performance appraisal, and training needs efficiently. The management support is critical in deploying automated HRIS to enhance output in agricultural companies. The deployment of HRIS systems isbeneficial for enhancingoutput in agricultural companies. However, before the deployment of such systems, the size of the organization, environment, type of business, and sensitivity of the information need to be considered. Employees will benefit as they are better equipped to visualize original ideas with enhanced IT capacities.